Hearing "that's so gay" and "no homo" on academic outcomes for LGBQ + college students. Issue 3 (3rd July 2019) - Mathies, Nicole; Coleman, Todd; McKie, Raymond M.; Woodford, Michael R.; Courtice, Erin Leigh; Travers, Robb; Renn, Kristen A.
Abstract: Heterosexist phrases on college campuses can contribute to negative consequences among lesbian, gay, bisexual, queer, and other sexual minority students (LGBQ+), however, their relationship to academic outcomes remains under-researched. This analysis investigates hearing the microaggressions "that's so gay" and "no homo" on academic engagement outcomes among a national sample of cisgender sexual minority college students ( n  = 574). The multivariable regression analysis suggest that increased exposure to hearing "that's so gay" and "no homo" were both significantly associated with worse academic outcomes in terms of developmental challenge ( p = .002 and p < .001, respectively). Greater instances of hearing "no homo" was also associated with lower college GPA scores ( p = .015). Strategies for educational institutions, faculty, and students to promote more accepting campus climates and alleviate the harmful effects of hearing these phrases are discussed.